The Challenge of Effective Family/School Partnerships: The Middle School Parent Teacher Leadership Academy Pilot Program - Blake Berryhill; Holly Morgan; Elizabeth Wilson; Hannah Ruggles (The University of Alabama, 2022)
Research supports the idea that positive family/school community partnerships during middle school can enhance student success. Thus schools are partnering with local universities to increase school and student outcomes. In order to support local middle schools, The University of Alabama created the Middle School Parent Teacher Leadership Academy, a training program that prepares middle school parent and teacher leaders with the skills to strengthen school and student outcomes. Using a mixed methods design, we analyzed pilot data from the first year of the Academy on parents' and teachers' leadership behaviors and self-efficacy. Pretest and posttest results showed that parent and teacher participants significantly increased their leadership behaviors. Qualitative thematic analysis revealed answers to the question: "What has the Academy meant to you?" as follows: 1) Facilitates parent-teacher collaboration, 2) Increases parent and teacher school leadership behaviors, 3) Enhances parent and teacher school leadership self-efficacy, 4) Increases opportunities for school change, and 5) Increases parental-school involvement. Implications and future directions are discussed.